Whether to write or not a dilemma in the professional role but a social necessity - Manuel Gregorio Loza-Murguia (Journal of the Selva Andina Research Society)
When we ask ourselves whether it is necessary to write the final results of a research or not, we must be clear about the reason, sometimes we believe that it is an obligation, but if we analyses this fact, it is not so, because if it is, there would be endless situations when it comes to carrying it out, as it would be a waste of time and resources. Let us not forget that research, depending on its level and degree of complexity, requires different materials, equipment, reagents, inputs and so on, hence the economic investment, and if it is not published, it would be a lack of understanding of why the research should be done. Some professionals in our environment talk a lot about research and what can be done, of such work or not, but in the end they are content to do their work, but forget to write, possibly due to lack of initiative or ignorance, although this is in doubt, since there are quite renowned media organizations whose demands on writing are considerable. But that is the core of a research, whether or not the research was actually done, must be written down. In some universities, publications are valued and in particular if that professional or group of professionals publish, which results in an increase in their salary, it seems that this is the central axis of writing or not, in our environment it is not clear how this work will be valued or to what extent support will be given to the professional who, in addition to researching, also publishes. It is necessary that the assigned authorities change course in their decision making and see with greater clarity the fact of giving a certain reward to the professionals who are silently carrying out research and giving rise to publication. Let us not forget that when articles are published, the authors' affiliation and the institution in which they work come to light, so it is not easy to write or not, it is already a reality and it is growing in our environment, but what about support or recognition, or should we just be Quixote’s of science, while some authorities do not give support and perhaps institutional recognition. All of the above should be based on a defined logic in an institution, few have in their organizational chart the department, committee, ethics, which evaluates whether or not such research work in undergraduate or postgraduate or in research projects, who would be responsible for certifying a particular topic and its relevance. As can be seen, this will continue to grow and perhaps it will not be possible to say "how I do such and such work", and what is worse, who accredits that researcher, if for some reason, his or her publication is requested to be presented at a national or international congress, then it is there that these researchers who were in the shadows come to light, but we must continue and make people feel that we are here, we are alive, we need to be taken into account, we are.... This note, insofar as it is considered by the different bodies, seeks to continue to maintain the strength of these professionals who are dedicated to writing, but are not recognized, but in time they will be the ones who will have to take decisions that mark the path and stop being invisible in an institution, whether it is a university or not.